Reading Comprehension Ability of German Descriptive Text - Zari Jumatrianinur; Nurming Saleh; Mantasiah R (Universitas Negeri Makassar, 2025)
Abstract. This research is a qualitative descriptive research that aim to determine the reading comprehension ability of German language descriptive text of students at SMA Negeri 3 Makassar. To determine the reading comprehension ability of German language descriptive texts, data was collected from 32 students from class XII10. The data were obtained through the results of reading comprehension ability tests consisting of three types of tests, namely multiple choice, true-false and questions about the text. The data obtained were analyzed using percentage techniques. The results of this study indicate that the reading comprehension ability of German language descriptive text of class XII10 students of SMA Negeri 3 Makassar is good category (78%).Keyword: Ability, Reading Comprehension, Text, Deskriptive